Architectonic and Rural Space in Ancient Greek Tragedy: Examples from Aeschylus and Euripides - Loukaki, Argyro (Actual Problems of Theory and History of Art, 2023)
The exploration of the nature of space and of spatial archetypes has been very important in ancient Greek thought and art, including ancient theatre. Focusing on Aeschylus’ Prometheus Bound (PB) and Euripides’ Bacchae (B), this paper investigates the aspects of the following archetypes as they emerge in Athenian tragedy:1. Architectonic space earlier than, as well as contemporary with Euripides, as conceived and represented through his sophisticated architectonic awareness and imagination.2. The role of mountains, as exemplified through Cithaeron and the Caucasus, theaters of tragic epiphanies of gods Dionysus and Prometheus in B and PB respectively. Both tragedies unfold in the earthly sphere, even if in Prometheus Bound the troupe is divine. However, while Cithaeron lies in the heart of the Greek world forming a natural background to the city of Thebes in Boeotia, the Caucasus lies on its edge. Alluring Dionysus, the master of Cithaeron in Bacchae, represents moral and natural powers that threaten defiant humans, while tormented Prometheus epitomizes divine support for human dignity and wellbeing.3. An interpretation of the city of Thebes in Boeotia as the locus of many Athenian tragedies.4. Also, a brief reference to the aesthetic categories of the sublime, the beautiful and the uncanny, as they appear in ancient drama. Philosophical exploration of morality and beauty are reverberated in the vigilant concern with the moral aspect of splendor.
Keywords: ancient tragedy; aesthetics; Cithaeron; Caucasus; tragic mountains; Dionysus and Prometheus; Thebes in Athenian tragedy; Aeschylus; Euripides and architecture